Word Box Intervention Revolutionizes Early Literacy Potential in Education: Intervensi Kotak Kata Merevolusi Potensi Literasi Dini dalam Pendidikan - Nikmah, Mafrukhatun; Destiana, Evie (Indonesian Journal of Innovation Studies, 2024)
his study investigates the efficacy of utilizing the "Word Box" media to enhance beginning reading skills among 5-6-year-old children in a preschool setting. Through a classroom action research (PTK) approach involving 12 participants, the study demonstrates a significant improvement in beginning reading proficiency from 17% in the pre-cycle to 83% in cycle II. The findings underscore the effectiveness of the intervention in improving early literacy skills and highlight its implications for teacher pedagogy and classroom management in preschool education. Highlight: Notable improvement: "Word Box" enhances beginning reading in preschoolers. Effective method: Innovative teaching fosters early literacy development. Pedagogical impact: Improves teacher skills and classroom management in preschool education. Keyword: Beginning reading, Preschool education, Classroom action research, Word Box media, Literacy development